Factors Affecting Sleep Quality of Breast Cancer Patients with Chemotherapy - Putri, Diyanah Syolihan Rinjani; Makiyah, Sri Nabawiyati Nurul (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Poor sleep quality becomes the effect of chemotherapy in breast cancer patients. AIM: This study aimed to examine the factors that influence breast cancer patients’ sleep quality undergoing chemotherapy. METHODS: This research used an observational method with cross-sectional design. There were 26 breast cancer patients undergoing chemotherapy at Djojonegoro Regional Hospital in Temanggung, Central Java. The characteristics of the respondent are recorded, including the demographic characteristics, respondents’ sleep quality, and the physiological status data of the respondent. The researchers use the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. Data were analyzed using Kendall’s Tau and Spearman’s rank correlation test and the Pearson Product-Moment Correlation test. RESULTS: The result showed that breast cancer patients’ sleep quality is classified as poor with PSQI score of 10.96 ± 3.13. The average age of the respondent was 50.08 ± 7.31 years. The major characteristic of the respondent were 80.77% had married, 42.30% had elementary education, 61.54% did not work, and 61.54% had Rp 0, - income. Based on breast cancer patients undergoing chemotherapy, the respondents lived in rice field environment (42.30%), diagnosed with breast cancer <1 year (69.23%), had <1 year chemotherapy (96.15%), had under mastectomy on the left breast (80.76%), and underwent chemotherapy as much as 7.23 ± 4.80 times. Based on sleep quality, the respondents lived with nuclear family (61.54%), had no comorbidities (76.92%), did not consume other drugs (100%), did not consume sleeping pills (80.76%), and used lights during sleep (65.38%). There is a correlation between sleep quality and age and with whom the respondent lives in the same house. CONCLUSION: It was concluded that breast cancer patients undergoing chemotherapy had poor sleep quality, and the factors related to sleep quality were age and with whom the respondent lived in the same house.